Sport Entrepreneur (Sport Massage) untuk Peningkatan Kesejahteraan Masyarakat Desa Jungsemi Kecamatan Kangkung Kabupaten Kendal Tahun 2020 - Valdyan Drifanda; Maftukin Hudah; Rosalina Ginting (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Jungsemi is a village that has a beautiful beach. The village is currently under development to become a jetski sports center. This village also has a takraw club. The objectives of community service are: (1) providing knowledge and theories about Sport Entrepreneurs and Injury Management with a Sport Massage Approach. (2) providing Sport massage skills for prevention, health and healing, and (3) providing skills and opportunities for residents to open a Sport massage business. The method used in this program are lecture, discussion, demonstration, and practice. Activity of handling injury with Sport Massage Approach for the People of Jungsemi Village, Kangkung District Kendal Regency, was held in the hall of Platar Village Hall with 35 people participating. The results of the activities are as follows: (1) residents of Jungsemi Village, Kangkung Subdistrict, Kendal District 2020, realize that Sport Entrepreneurs and massage in handling injuries with the Sports Massage approach, (2) Platar villagers are satisfied with the results of the training and expect training to be held at the stages more broadly about the knowledge of handling injury with sport massage